Les logiques d’interprétation des enfants selon leur expérience de visite dans les musées de sciences et dans le cadre des loisirs - Thérèse Martin (Communication)
Within the frameworks of leisure and of cultural practices of museums, the author of this research brief is interested in the children’s experience of museums, especially their modes of appropriation. Her aim is to describe and to understand the children’s interpretation during a scheduled visit of exhibits. The analysis of the children’s verbal accounts enabled the author to delineate the frameworks in which they interpret the discursive spaces of the exhibits, as well as to recognize four types of child-interpreter in varying modes of appropriation.